Self-powered Infusion Micropump Fabrication Using Xurography and Thermal Lamination Techniques - Idris, Zul Fadhli; Abidin, Ummikalsom; Md Sunhazim, Nur Shamimi Amirah (International Journal of Integrated Engineering, 2022)
Point of care testing (POCT) as part of diseases and health monitoring will be very beneficial in resource constrained areas with minimum healthcare expert and power requirement. Elimination of external power source in testing device brought the idea of self-powered infusion micropump. This research aimed to fabricate and investigate the pumping capability of non-mechanical self-powered infusion micropump under the effect of different porous materials. The self-power infusion micropump was successfully fabricated with Xurography and thermal-lamination techniques. The average percentage difference between the measured dimensions of micropump with actual design was 2.30 %. Sandwich layers configuration of the micropump which consisted of PVC sheet and laminating plastic pouch was successfully fabricated and proven to have a leak-proof micropump. Micropump’s flow rate of 0.89, 3.62, and 0.84 μL/min were obtained under the effect of porous material ashless grade Whatman filter paper number W40, W41 and W42 respectively. These flow rate values were influenced by filtration speed as per porous material specifications.